Artificial intelligence in academic literacy: empirical evidence on reading and writing practices in higher education - Baldrich, Kevin; Pérez-García, Carmen; Santamarina-Sancho, María (Frontiers in Education, 2025)
Academic reading and writing constitute fundamental competences in higher education that enable access to disciplinary knowledge and participation in academic communities. The incorporation of Artificial Intelligence has transformed these practices, yet empirical research examining validated instruments to measure students‘ beliefs, perceptions, and practices remains incipient. This systematic review followed PRISMA 2020 guidelines to identify empirical studies that examine the use of AI tools in university students' reading and writing processes, specifically locating surveys, questionnaires, and methodologies with clear information on their design, validation, and application adaptable for future studies in academic literacy. The search in Scopus and Web of Science between January 2023 and April 2025 yielded 4,248 initial results, with 55 studies meeting inclusion criteria after rigorous screening based on empirical content with validated instruments and minimum sample requirements. The corpus reveals predominance of quantitative methodologies with instruments developed and subjected to rigorous statistical validation, including the ChatGPT Usage Scale, AILS-CCS scale measuring four AI literacy dimensions, SIUAIT index for institutional integration, and adaptations of technology acceptance models (TAM, TPB, UTAUT). Students employ AI primarily for idea generation, text structuring, and revision, driven by perceived usefulness, intrinsic motivation, and facilitating conditions. The findings demonstrate five critical themes: AI impact on academic skills development, ethical concerns regarding integrity and authorship, need for critical digital literacy, disparities between perceptions and preparedness, and necessity for redefining assessment methods. These validated instruments provide a methodological foundation for future research, as institutions require empirical tools to guide pedagogical integration of AI as a complementary resource within academic literacy frameworks.